Newton's Sleep - Tallis, R. author. aut Link
XX, 260 p.
Keywords: 'Vast in its intellectual scope, it should induce not so much sleep as controversy, whether literary or scientific, philosophical or political. It skims the oceans of academe in a manner accessible to the educated public, informed and cogently argued, stylistically dense...' - Sandra Goldbeck-Wood, British Medical Journal `Tallis can, and frequently does, write extremely well. He also writes with considerable passion...Raymond Tallis, is perhaps best seen as an exceptionally interesting and broad-minded heir to Huxley, preaching the cause of the Church Scientific.' - Richard Webster, Times Literary Supplement Reviews of Not Saussure and The Explicit Animal: Not Saussure - 'I greatly enjoyed it...' - Bernard Bergonzi 'The Explicit Animal - '...his books are genuine contributions to professional debate...' - Stephen R.L. Clarke, Times Literary Supplement Newton's Sleep examines the complementary roles of science and art in human life. Science has been criticised for being at best useful but spiritually derelict, and art for attempting to answer the spiritual needs of humankind while ignoring the material needs of millions who live in want. Newton's Sleep deals with the charges that science is spiritually empty and that art fails in its civilising mission by relating these aspects of human culture to the physical and metaphysical hungers of an explicit animal who lives in both the Kingdom of Means and the Kingdom of Ends. 'Tallis can, and frequently does, write extremely well. He also writes with considerable passion...Tallis...is perhaps best seen as an exceptionally interesting and broad-minded heir to Huxley, preaching the cause of the Church Scientific...' Richard Webster.